Lithium ion sieve polymer composite membrane as well as preparation method and application thereof
By introducing hydrophilic monomers in the preparation process of lithium ion sieve membrane and integrating its polymerization and crosslinking process into the crosslinking network of hydrophobic polymers, the shortcomings in the adsorption capacity and kinetic performance of the existing lithium ion sieve membrane are solved, and a lithium ion sieve polymer composite membrane with high mechanical strength, high adsorption capacity and fast kinetic performance are achieved.
Patent Information
- Application Number
- CN202510215172.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-26
AI Technical Summary
The existing lithium-ion sieve membranes have shortcomings in adsorption capacity and kinetic properties, and have poor mechanical strength and stability, making it difficult to meet the needs of industrial applications.
By introducing hydrophilic monomers, the curing process with hydrophobic monomers is carried out in steps, and the polymerization and cross-linking process of hydrophilic monomers is integrated into the cross-linking network of hydrophobic polymers, and a lithium-ion sieve polymer composite film with high mechanical strength, high adsorption capacity, and high adsorption kinetic properties is prepared.
It realizes the high mechanical strength and high adsorption capacity of the lithium ion sieve membrane, while improving the wettability and kinetic properties of the membrane, promoting the rapid adsorption of lithium, and is suitable for industrial applications.
Smart Images

Figure CN119909548A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion sieves and relates to a lithium ion sieve polymer composite membrane and a preparation method and application thereof. Background Art
[0002] With the rapid development of science and technology in recent years, lithium and its compounds play an extremely important role in the fields of chemical industry, glass, ceramics, metallurgy, medicine, lubricants, nuclear energy, and especially batteries. At present, lithium resources are mainly stored in salt lake brine. However, due to the low lithium ion concentration and relatively high impurity content in salt lake brine, it is necessary to develop highly selective and efficient salt lake raw brine lithium extraction technology. The lithium ion sieve continuous adsorption method is used to extract lithium from salt lakes. It has the advantages of simple process, low energy consumption, easy scalability, and suitability for low lithium concentration systems. Therefore, it has the potential for industrialization.
[0003] The ion sieve powder prepared in the prior art is usually micron-sized or nano-sized, which results in poor fluidity and permeability when used directly, and a large pressure drop during column adsorption. Therefore, the ion sieve needs to be formed before it can play a role in practical applications. Membrane forming is an emerging ion sieve forming method, which is usually performed by dispersing the ion sieve in an organic solvent mainly composed of hydrophobic monomers, and then curing it into a film by solvent volatilization. Although the ion sieve membrane made by this method has high mechanical strength and stability, it has a low adsorption capacity and slow kinetic performance.
[0004] Based on the above research, it is necessary to provide a method for preparing a lithium ion sieve, which can quickly prepare a lithium ion sieve membrane with high mechanical strength, high adsorption capacity, high adsorption kinetics and high selectivity. Summary of the invention
[0005] The object of the present invention is to provide a lithium ion sieve polymer composite membrane and a preparation method and application thereof. The preparation method introduces a hydrophilic monomer so that the curing process of the hydrophilic monomer and the hydrophobic monomer is carried out step by step, and the polymerization and cross-linking process of the hydrophilic monomer is integrated into the cross-linking network of the hydrophobic polymer. This not only maintains the mechanical strength of the lithium ion sieve polymer composite membrane, but also improves the wettability of the membrane and exposes more active sites, thereby promoting the rapid adsorption of lithium, and obtaining a lithium ion sieve polymer composite membrane with high mechanical strength, high adsorption capacity, high adsorption kinetics and high selectivity.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a lithium ion sieve polymer composite membrane, the preparation method comprising the following steps:
[0008] (1) mixing a lithium ion sieve precursor, a hydrophobic polymer, a solvent, a hydrophilic monomer and a photoinitiator to obtain a film casting solution;
[0009] (2) forming a film with the casting solution of step (1) to obtain a wet film;
[0010] (3) The wet film of step (2) is first photocured, then dried and cured, and finally post-treated to obtain the lithium ion sieve polymer composite membrane.
[0011] The present invention prepares a composite membrane by photoinitiated polymerization and solvent volatilization. The hydrophilic monomer is first polymerized by photocuring, and then the solvent is volatilized by drying and curing to achieve the curing of the hydrophobic polymer. The curing process of the hydrophilic monomer and the hydrophobic polymer is carried out step by step. In addition, the hydrophilic monomer is polymerized in the cross-linked structure of the hydrophobic polymer during photocuring, that is, the cross-linked polymerization process of the hydrophilic monomer can be integrated into the cross-linked network of the hydrophobic polymer. This not only maintains the mechanical strength of the lithium ion sieve polymer composite membrane, but also improves the wettability of the lithium ion sieve polymer composite membrane, creates a richer pore structure, and exposes more active sites, thereby promoting the rapid adsorption of lithium, and preparing a lithium ion sieve polymer composite membrane with high mechanical strength and stability, high adsorption capacity and rapid kinetic performance.
[0012] Preferably, the mass ratio of the hydrophobic polymer to the hydrophilic monomer in step (1) is 1:(0.5-5), for example, it can be 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5, but is not limited to the listed values. Other values not listed within the numerical range are also applicable, preferably 1:(1-5).
[0013] The mass ratio of the hydrophobic high molecular polymer and the hydrophilic monomer of the present invention will affect the wettability and mechanical properties of the lithium ion sieve polymer composite membrane. If the hydrophilic monomer is relatively small, its effect will be reduced. If the hydrophilic monomer is relatively large, the hydrophilic monomer will be dissolved in the polymer composite membrane in water, which will lead to poor stability of the membrane, poor mechanical properties and high swelling rate, which will easily cause the loss of ion sieve powder and affect the service life of the ion sieve composite membrane.
[0014] Preferably, the amount of the hydrophilic monomer added in step (1) is 1-50wt% of the total mass of the casting solution, for example, it can be 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 6.25-25wt%.
[0015] Preferably, the hydrophilic monomer in step (1) is a hydrophilic monomer capable of undergoing a photoinitiated free radical polymerization reaction, including any one of polyvinyl monomers (polyethylene glycol diacrylate, polyethylene glycol acrylate), N-vinyl pyrrolidone, acrylic acid, acrylic acid derivatives, methacrylic acid, methacrylic acid derivatives, acrylamide or acrylamide derivatives, or a combination of at least two thereof.
[0016] Among the preferred hydrophilic monomers of the present invention, the carbon-carbon double bonds in the polyvinyl monomers (which can be polymerized and can also become monomers) can be free radically polymerized, the carbon-carbon double bond groups of N-vinyl pyrrolidone can be free radically polymerized, the carbon-carbon double bonds of polyethylene glycol acrylate (which can be polymerized and can also become monomers) can be free radically polymerized, and the carbon-carbon double bonds of acrylamide can be free radically polymerized.
[0017] Preferably, the amount of the hydrophobic high molecular polymer added in step (1) is 2-90wt% of the total mass of the casting solution, for example, it can be 2wt%, 5wt%, 8wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt% or 90wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable, preferably 5-10wt%.
[0018] Preferably, the hydrophobic high molecular polymer in step (1) comprises any one of polyvinyl chloride, polyacrylonitrile or polyvinylidene fluoride (PVDF) or a combination of at least two thereof.
[0019] Preferably, the lithium ion sieve precursor in step (1) includes a manganese-based lithium ion sieve precursor and / or a titanium-based lithium ion sieve precursor.
[0020] Preferably, in the lithium ion sieve polymer composite membrane, the loading amount of the lithium ion sieve precursor in step (1) is 20-150wt%, for example, it can be 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 100wt%, 110wt%, 120wt%, 130wt%, 140wt% or 150wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] The loading amount of the lithium ion sieve precursor in the present invention refers to the percentage of the mass of the lithium ion sieve precursor to the total mass of the dry film.
[0022] Preferably, the mixing in step (1) comprises first mixing the lithium ion sieve precursor, the hydrophobic polymer and the solvent to obtain a mixed solution, and then mixing the mixed solution with the hydrophilic monomer and the photoinitiator.
[0023] Preferably, the solvent in step (1) comprises any one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide, or a combination of at least two thereof.
[0024] Preferably, the mass ratio of the hydrophobic polymer to the solvent in step (1) is 1:(5-50), for example, 1:5, 1:10, 1:20, 1:30, 1:40 or 1:50, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the mass ratio of the hydrophilic monomer to the photoinitiator in step (1) is 1:(0.005-0.02), for example, it can be 1:0.005, 1:0.01, 1:0.015 or 1:0.02, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the film-forming method in step (2) comprises coating the casting solution on a glass plate to form the film,
[0027] Preferably, the thickness of the wet film in step (2) is 200-300 μm, for example, 200 μm, 225 μm, 250 μm, 275 μm or 300 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, ultraviolet light is used to perform the photocuring in step (3);
[0029] Preferably, the power of the photocuring in step (3) is 120-280 W, for example, 120 W, 160 W, 200 W, 240 W or 280 W, and the time is 2-5 min, for example, 2 min, 3 min, 4 min or 5 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0030] Preferably, the drying and curing temperature in step (3) is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C, and the drying and curing time is 1-5h, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the post-treatment in step (3) includes washing and acid leaching.
[0032] In a second aspect, the present invention provides a lithium ion sieve polymer composite membrane, wherein the lithium ion sieve polymer composite membrane is prepared by the preparation method described in the first aspect.
[0033] In a third aspect, the present invention provides an application of the lithium ion sieve polymer composite membrane as described in the second aspect, wherein the application includes use for extracting lithium from salt lakes.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The preparation method of the present invention adopts hydrophobic polymer and hydrophilic monomer to realize the preparation of lithium ion sieve polymer composite membrane, which not only ensures the mechanical strength of the lithium ion sieve composite membrane, but also ensures the contact area between the composite membrane and the brine, improves the mass transfer rate, and can achieve efficient adsorption of lithium;
[0036] (2) The hydrophilic monomers of the present invention polymerize in the cross-linked structure of the hydrophobic polymer, thereby improving the wettability and hydrophilicity of the membrane, increasing the contact area between the lithium ion sieve and the brine, and facilitating the improvement of the mass transfer rate and adsorption capacity. In addition, the adsorption effect and selectivity of the lithium ion sieve polymer composite membrane can be improved by selecting different hydrophilic monomers and regulating the concentration of the hydrophilic monomers.
[0037] (3) The preparation method of the present invention adopts photo-initiated polymerization and solvent evaporation to prepare the lithium ion sieve polymer composite membrane, and the preparation process is simple and can be applied industrially. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM image of the lithium ion sieve polymer composite membrane described in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane, the preparation method comprising the following steps:
[0042] (1) 3 g of polyvinyl chloride powder and 6 g of lithium ion sieve precursor Li 2 TiO 3 Add to 48 g of N,N-dimethylformamide solution, use ultrasonic dispersion technology at room temperature to evenly disperse the powder in the solution, and then use a mechanical stirrer to stir at room temperature for 12 hours to ensure that the mixture is completely uniform;
[0043] In step (1), the amount of polyvinyl chloride added is 5wt% of the total mass of the casting solution, the loading amount of the lithium ion sieve precursor is 40wt%, and the mass ratio of the polyvinyl chloride powder to N,N-dimethylformamide is 1:16;
[0044] (2) Add 6 g of polyethylene glycol diacrylate (PEGDA600) and 60 mg of photoinitiator 2959 to the above homogeneous mixture, and continue mechanical stirring at room temperature for 24 h to ensure that all components are fully mixed to form a homogeneous casting solution;
[0045] The photoinitiator 2959 is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0046] The mass ratio of the polyvinyl chloride to polyethylene glycol diacrylate is 1:2;
[0047] The amount of polyethylene glycol diacrylate added is 10wt% of the total mass of the casting solution;
[0048] The mass ratio of the polyethylene glycol diacrylate to the photoinitiator is 1:0.01;
[0049] (3) The prepared casting solution was evenly coated on a glass plate, the wet film thickness was controlled to be 300 μm, and the coated wet film was placed under a 150 W ultraviolet lamp for 3 min of UV curing;
[0050] (4) The UV-cured wet film was transferred to an oven at 60 °C and continued to cure for 4 h to ensure that the material was fully cured.
[0051] (5) After drying, washing and acid leaching are performed to obtain the lithium ion sieve polymer composite membrane. The SEM image of the lithium ion sieve polymer composite membrane is as follows: Figure 1 shown.
[0052] Example 2
[0053] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane, the preparation method comprising the following steps:
[0054] (1) 3 g of polyvinyl chloride powder and 60 g of lithium ion sieve precursor Li 2 TiO 3 Add to 60 mL of N,N-dimethylformamide solution, use ultrasonic dispersion technology at room temperature to evenly disperse the powder in the solution, and then use a mechanical stirrer to stir at room temperature for 12 h to ensure that the mixture is completely uniform;
[0055] In step (1), the amount of polyvinyl chloride added is 5wt% of the total mass of the casting solution, the loading amount of the lithium ion sieve precursor is 70wt%, and the mass ratio of the polyvinyl chloride powder to N,N-dimethylformamide is 1:20;
[0056] (2) Add 15 g of polyethylene glycol diacrylate (PEGDA600) and 300 mg of photoinitiator 2959 to the above homogeneous mixture, and continue mechanical stirring at room temperature for 24 h to ensure that all components are fully mixed to form a homogeneous casting solution;
[0057] The photoinitiator 2959 is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0058] The mass ratio of the polyvinyl chloride to polyethylene glycol diacrylate is 1:5;
[0059] The amount of polyethylene glycol diacrylate added is 25wt% of the total mass of the casting solution;
[0060] The mass ratio of the polyethylene glycol diacrylate to the photoinitiator is 1:0.02;
[0061] (3) The prepared casting solution was evenly coated on a glass plate, the wet film thickness was controlled to be 200 μm, and the coated wet film was placed under a 280 W ultraviolet lamp for 2 min of UV curing;
[0062] (4) The UV-cured wet film was transferred to an oven at 70 °C and continued to cure for 3 h to ensure that the material was fully cured.
[0063] (5) After drying, washing and acid leaching are performed to obtain the lithium ion sieve polymer composite membrane.
[0064] Example 3
[0065] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane, the preparation method comprising the following steps:
[0066] (1) 3 g polyvinylidene fluoride powder (PVDF) and 6 g lithium ion sieve precursor Li 2 TiO 3 Add to 36 mL of N,N-dimethylformamide solution, use ultrasonic dispersion technology at room temperature to evenly disperse the powder in the solution, and then use a mechanical stirrer to stir at room temperature for 12 h to ensure that the mixture is completely uniform;
[0067] In step (1), the amount of polyvinylidene fluoride added is 6.25wt% of the total mass of the casting solution, the loading amount of the lithium ion sieve precursor is 40wt%, and the mass ratio of the polyvinylidene fluoride powder to N,N-dimethylformamide is 1:12;
[0068] (2) Add 3 g of polyethylene glycol diacrylate (PEGDA600) and 15 mg of photoinitiator 2959 to the above homogeneous mixture, and continue mechanical stirring at room temperature for 24 h to ensure that all components are fully mixed to form a homogeneous casting solution;
[0069] The photoinitiator 2959 is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone;
[0070] The mass ratio of the polyvinylidene fluoride to polyethylene glycol diacrylate is 1:1;
[0071] The amount of polyethylene glycol diacrylate added is 6.25wt% of the total mass of the casting solution;
[0072] The mass ratio of the polyethylene glycol diacrylate to the photoinitiator is 1:0.005;
[0073] (3) The prepared casting solution was evenly coated on a glass plate, the wet film thickness was controlled to be 250 μm, and the coated wet film was placed under a 120 W ultraviolet lamp for UV curing for 5 min;
[0074] (4) The UV-cured wet film was transferred to an oven at 50 °C and continued to cure for 5 h to ensure that the material was fully cured.
[0075] (5) After drying, washing and acid leaching are performed to obtain the lithium ion sieve polymer composite membrane.
[0076] Example 4
[0077] The present embodiment provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as that of Example 1 except that the mass ratio of polyvinyl chloride to polyethylene glycol diacrylate is 1:0.5 and the amount of the hydrophilic monomer polyethylene glycol diacrylate added is reduced.
[0078] Example 5
[0079] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as that of Example 1 except that the mass ratio of polyvinyl chloride to polyethylene glycol diacrylate is 1:7 and the amount of hydrophilic monomer polyethylene glycol diacrylate added is increased.
[0080] Example 6
[0081] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as that of Embodiment 1 except that the mass of polyethylene glycol diacrylate is replaced by N-vinyl pyrrolidone.
[0082] Example 7
[0083] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as that of Embodiment 1 except that polyethylene glycol diacrylate is replaced by polyethylene glycol acrylate.
[0084] Example 8
[0085] This embodiment provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as that of Embodiment 1 except that polyethylene glycol diacrylate is replaced by acrylamide.
[0086] Comparative Example 1
[0087] This comparative example provides a method for preparing a lithium ion sieve polymer composite membrane. The preparation method is the same as Example 1 except that the UV curing described in step (2) and step (3) is not performed. That is, this comparative example does not add a hydrophilic monomer and a photoinitiator, and does not perform ultraviolet light curing.
[0088] The lithium ion sieve polymer composite adsorption capacity obtained in the above examples and comparative examples is tested by the following method: the lithium ion sieve polymer composite membrane is mixed with 50 mg·L -1 LiCl solution (pH = 13) at 1 g·L -1 The lithium ion sieve polymer composite membrane is kept fully oscillating in the solution at room temperature, and the evenly oscillated solution is extracted at specific intervals to determine the Li concentration in the solution at this time, and the adsorption capacity of the ion sieve membrane is calculated. The adsorption capacity-time curve is drawn to obtain the adsorption equilibrium time and equilibrium concentration of the lithium ion sieve membrane. The test results are shown in Table 1:
[0089] Table 1
[0090]
[0091]
[0092] From Table 1 we can see that:
[0093] It can be seen from Example 1 and Comparative Example 1 that the preparation method of the present invention significantly improves the adsorption capacity of the lithium ion sieve polymer composite membrane and reduces the adsorption equilibrium time by adding a hydrophilic monomer to the casting liquid and polymerizing it in the cross-linked network of the hydrophobic polymer by photocuring; it can be seen from Example 1 and Examples 4-5 that the amount of hydrophilic monomer added in the present invention will affect the performance of the lithium ion sieve polymer composite membrane; it can be seen from Examples 1 and Examples 6-8 that when the type of the hydrophilic monomer of the present invention changes, the performance of the lithium ion sieve polymer composite membrane also changes. Since PEGDA600 has a higher adsorption capacity and a faster equilibrium time, the preferred hydrophilic monomer of the present invention is PEGDA600.
[0094] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium ion sieve polymer composite membrane, characterized in that: The preparation method comprises the following steps: (1) mixing a lithium ion sieve precursor, a hydrophobic polymer, a solvent, a hydrophilic monomer and a photoinitiator to obtain a film casting solution; (2) forming a film with the casting solution of step (1) to obtain a wet film; (3) The wet film of step (2) is first photocured, then dried and cured, and finally post-treated to obtain the lithium ion sieve polymer composite membrane.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the hydrophobic polymer to the hydrophilic monomer in step (1) is 1:(0.5-5), preferably 1:(1-5); Preferably, the amount of the hydrophilic monomer added in step (1) is 1-50wt% of the total mass of the casting solution, preferably 6.25-25wt%; Preferably, the hydrophilic monomer in step (1) comprises any one or a combination of at least two of polyvinyl monomers, N-vinyl pyrrolidone, acrylic acid, acrylic acid derivatives, methacrylic acid, methacrylic acid derivatives, acrylamide or acrylamide derivatives; Preferably, the polyvinyl-based monomer includes polyethylene glycol diacrylate and / or polyethylene glycol acrylate.
3. The preparation method according to claim 1 or 2, characterized in that: The amount of the hydrophobic polymer added in step (1) is 2-90wt% of the total mass of the casting solution, preferably 5-10wt%; Preferably, the hydrophobic high molecular polymer in step (1) includes any one of polyvinyl chloride, polyacrylonitrile or polyvinylidene fluoride, or a combination of at least two thereof.
4. The preparation method according to any one of claims 1 to 3, characterized in that The lithium ion sieve precursor in step (1) includes a manganese-based lithium ion sieve precursor and / or a titanium-based lithium ion sieve precursor; Preferably, in the lithium ion sieve polymer composite membrane, the loading amount of the lithium ion sieve precursor in step (1) is 20-150wt%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mixing in step (1) comprises first mixing a lithium ion sieve precursor, a hydrophobic polymer and a solvent to obtain a mixed solution, and then mixing the mixed solution with a hydrophilic monomer and a photoinitiator; Preferably, the solvent in step (1) comprises any one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or dimethyl sulfoxide, or a combination of at least two thereof; Preferably, the mass ratio of the hydrophobic polymer to the solvent in step (1) is 1:(5-50); Preferably, the mass ratio of the hydrophilic monomer to the photoinitiator in step (1) is 1:(0.005-0.02).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The film-forming method in step (2) comprises coating the casting solution on a glass plate to form a film; Preferably, the thickness of the wet film in step (2) is 200-300 μm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: Using ultraviolet light to perform the photocuring in step (3); Preferably, the power of the light curing in step (3) is 120-280W, and the time is 2-5min; Preferably, the drying and curing temperature in step (3) is 50-70° C. and the time is 1-5 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The post-treatment in step (3) includes washing and acid leaching.
9. A lithium ion sieve polymer composite membrane, characterized in that: The lithium ion sieve polymer composite membrane is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the lithium ion sieve polymer composite membrane as claimed in claim 9, characterized in that: The applications include use in extracting lithium from salt lakes.
Citation Information
Patent Citations
Preparation method and application of lithium-titanium type ion sieve composite membrane
CN106622170A
Porous membrane formed from interpenetrating polymer network having hydrophilic surface
US5158721A